1993
DOI: 10.1038/364771a0
|View full text |Cite
|
Sign up to set email alerts
|

Association of folding intermediates of glycoproteins with calnexin during protein maturation

Abstract: Calnexin, an endoplasmic reticulum transmembrane protein, represents a new type of molecular chaperone that selectively associates in a transient fashion with newly synthesized monomeric glycoproteins in HepG2 cells. Calnexin only recognizes glycoproteins when they are incompletely folded. Dissociation of glycoproteins from calnexin occurs at different rates and is related to the time taken for their folding, which may then initiate their differential transport rates from the endoplasmic reticulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
400
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 554 publications
(419 citation statements)
references
References 35 publications
18
400
1
Order By: Relevance
“…7, March 1996 491 tion is of low affinity very much like the initial binding of the chaperone calnexin to monoglucosylated glycoproteins in the ER (Ware et al, 1995). However, with calnexin, an additional polypeptide-polypeptide interaction appears to stabilize the initial carbohydrate binding which allows co-immunoprecipitation of the ligands (Degen et al, 1992;Ou et al, 1993;Hammond et al, 1994, Hebert et al, 1995Ware et al, 1995;Zhang et al, 1995). In contrast, our attempts to co-isolate ERGIC-53 and ligands by immunoprecipitation have not been successful (Itin, Bucher, and Hauri, unpublished results).…”
Section: Hypothesis Of Ergic-53 Functionmentioning
confidence: 66%
“…7, March 1996 491 tion is of low affinity very much like the initial binding of the chaperone calnexin to monoglucosylated glycoproteins in the ER (Ware et al, 1995). However, with calnexin, an additional polypeptide-polypeptide interaction appears to stabilize the initial carbohydrate binding which allows co-immunoprecipitation of the ligands (Degen et al, 1992;Ou et al, 1993;Hammond et al, 1994, Hebert et al, 1995Ware et al, 1995;Zhang et al, 1995). In contrast, our attempts to co-isolate ERGIC-53 and ligands by immunoprecipitation have not been successful (Itin, Bucher, and Hauri, unpublished results).…”
Section: Hypothesis Of Ergic-53 Functionmentioning
confidence: 66%
“…Inhibition of early glycan processing events leads to the retention and misfolding of some glycoproteins within the ER (15). This may be the result of triglucosylated glycoproteins being unable to interact with ER chaperones such as calnexin, which only recognize monoglucosylated glycoproteins (16,17). Inhibitors of ␣-glucosidase, an ER early glycan processing enzyme, have also been shown to have antiviral activities against many viruses, including HBV (10).…”
Section: Resultsmentioning
confidence: 99%
“…It is in this cellular compartment that protein folding, oligomerization, and the viral budding process occur (5). For glycoproteins, the processing of the initial oligosaccharide precursor from the Glc 3 Man 9 GlcNAc 2 glycoform to the Glc 1 Man 9 GlcNAc 2 glycoform in the ER can lead to an interaction with chaperones such as calnexin (16). Calnexin, which binds only to glycoproteins containing Glc 1 Man 9 GlcNAc 2 structures, is thought to assist the folding of some glycoproteins (17).…”
Section: Discussionmentioning
confidence: 99%
“…This idea was expanded by seminal work from Ou et al, who demonstrated that calnexin can associate with a whole range of glycosylated folding intermediates in the cell, and that their rate of release is related to the time taken for the protein to fold (Ou et al, 1993). Subsequently, calnexin has been found associated with many different ER glycoproteins, including the MHC class I loading complex (Jackson et al, 1994) (Vassilakos et al, 1996) (Sadasivan et al, 1996) (Harris et al, 1998 and transferrin .…”
Section: Calnexin and Calreticulinmentioning
confidence: 95%